2007
DOI: 10.1590/s1413-86702007000100021
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and pathogenesis of bloodstream infections associated with the use of long-term central vascular catheter (CVC) in patients who undergone gastrointestinal surgery

Abstract: CVC is the main factor of risk of bloodstream infections. This study purpose was determining both etiology and pathogenesis of these infections in 80 patients who undergone gastrointestinal surgery and who worn long lasting CVC, in the institution HC-UFU. Cultures were made in nostril, skin of the insertion site, tip and catheter hub, in addition to hemoculture in those suspects of sepsis. The colonization incidence rate of the catheter tip was 12.5/ 1,000 catheter days and the CVC associate infection rate was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
(18 reference statements)
0
0
2
1
Order By: Relevance
“…Lorente et al, (2005) and Brito et al, (2007) reported culture positivity as 2.04 % and 3.8% respectively which was lesser compared to the present study. The comparison of organisms isolated with other studies is shown in Table 2.…”
Section: Acinetobactercontrasting
confidence: 75%
See 1 more Smart Citation
“…Lorente et al, (2005) and Brito et al, (2007) reported culture positivity as 2.04 % and 3.8% respectively which was lesser compared to the present study. The comparison of organisms isolated with other studies is shown in Table 2.…”
Section: Acinetobactercontrasting
confidence: 75%
“…However, the reason for this high incidence in males could not be attributable to any reasons. CLABSI/CRBSI were common in the age group 51-60 years, in comparison with the study conducted by Brito et al, (2007), Apostolopoulou et al, (2009) and Datta et al, (2014). This could be attributable to the decreased immune status at that age group.…”
Section: Acinetobactercontrasting
confidence: 40%
“…Seu uso foi introduzido nos hospitais na década de 1940 e se tornou essencial para a prática médica moderna. Os cateteres são usados para a administração intravenosa de fluídos, drogas, nutrição parenteral e para o monitoramento hemodinâmico de pacientes em estado crítico (BRITO et al, 2007).…”
Section: Introductionunclassified